Federal Minimum Wage Hikes Do Reduce Teenage Employment: The Time Series Effects of Minimum Wages in the US Revisited - Stephen Bazen; Velayoudom Marimoutou (Institute for the Study of Labor (IZA), 2016)
In 2002 we published a paper in which we used state space time series methods to analyse the teenage employment-federal minimum wage relationship in the US (Bazen and Marimoutou, 2002). The study used quarterly data for the 46 year period running from 1954 to 1999. We detected a small, negative but statistically significant effect of the federal minimum wage on teenage employment, at a time when some studies were casting doubt on the existence of such an effect. In this note we re-estimate the original model with a further 16 years of data (up to 2015). We find that the model satisfactorily tracks the path of the teenage employment-population ratio over this 60 year period, and yields a consistently negative and statistically significant effect of minimum wages on teenage employment. The conclusion reached is the same as in the original paper, and the elasticity estimates very similar: federal minimum wage hikes lead to a reduction in teenage employment with a short run elasticity of around – 0.13. The estimated long run elasticity of between – 0.37 and – 0.47 is less stable, but is nevertheless negative and statistically significant.
Keywords: J21; J38; C22; 330; minimum wage; teenage employment; state space methods; unobserved components model